Contribuições para a epidemiologia da infecção por Leptospira sp. em animais silvestres no Estado da Paraíba - Bison, Ividy (2023)
Anthropogenic actions generate irreversible damage to nature, destroying the habitat of many wild animals. Urban and agricultural expansion into natural areas, along with trafficking activities, have increased the contact between these animals and humans, potentially resulting in the transmission of zoonotic diseases such as leptospirosis. This study aimed to characterize the epidemiological situation of leptospirosis in wild mammals from the state of Paraíba, sourced from the Center of Wild Animal Triage. Samples were collected from 90 wild mammals, with blood samples obtained from 65 animals subjected to serological analysis using the Microscopic Agglutination Test (MAT). Additionally, samples were collected from 34 animals that either arrived deceased or succumbed during the research, and these underwent necropsy for tissue sample collection. Of these, nine animals yielded both types of samples and passed away during the study period. Necropsy fragments were sent for molecular characterization through PCR. In the serological examination, nine (13.8%) animals exhibited seroreactivity, with antibodies against six serovars identified. Antibodies against the Pomona serovar were found in three animals (3/9), followed by Hebdomadis, Gryppotyphosa, Pyrogenes, Patoc, and Shermani. This study identified, for the first time, antibodies against Leptospira spp. in Sapajus spp. in Paraíba. In the molecular analysis, 12 out of 34 animals (34.3%) showed DNA amplification of Leptospira sp. for LipL32 in at least one collected organ. Six positive sloths were identified, with four having Leptospira sp. DNA in the brain. Pathogenic species are circulating in the wildlife of Paraíba, and monitoring along with further studies are necessary to understand the role of these animals in the epidemiology of leptospirosis.